OTH-11 Intelligent liver function testing (iLFT) in action. (June 2019) - Robinson, Emma; Nobes, Jennifer; Brennan, Paul; Dow, Ellie; Dillon, John
Abstract : Background and aims: Liver Function Tests (LFTs) are commonly requested and are abnormal in 20% of cases. Intelligent liver function testing (iLFT) aims to improve diagnostic proficiency and quality of investigation thereby reducing overall costs to practitioners and patients and subsequent secondary care referrals. Following a pilot trial, iLFT was rolled out across general practices in NHS Tayside from August 2018. Method: The automated iLFT algorithm uses the combination of clinical features (alcohol consumption, BMI and metabolic syndrome), diagnostic criteria for liver disease, an investigation ordering and reporting system, and the tracked blood sciences system to generate a diagnosis or descriptor of the abnormality with fibrosis staging. Management plans are disseminated back to the GP, along with a recommendation for one of three outcomes; a) secondary care follow up for advanced liver disease or complex treatment, b) primary care follow up of early or simple liver disease, c) where a clear diagnosis is unclear; the GP receives staging and prognostic information including referral criteria. Results of iLFT in action, over 6 months were analysed. Results: 777 iLFT requests over 6 months to 31/01/19. 568/777 requests had at least 1 abnormal LFT triggering the iLFT cascade. 169 (29.8%) were referred to secondary care, 399 (70.2%) patients were investigated further or managed in primary care. The most common finding was isolated ALT elevation without fibrosis (24.8%), followed by alcohol related liver disease without fibrosis(16.4%) then non-alcoholic fatty liver disease with fibrosis (8.1%) and elevated ALT and GGT without fibrosis (8.1%). There were 2 HBV infections, 8 HCV infections, 3 haemochromatosis diagnoses, 1 PBC and 1 A1AT PiS variant (risk of lung/liver disease) and 17 carriers of A1AT S or Z variant. Conclusion: Using iLFT; s erious liver disease has been detected and referred to secondary care. High numbers of LFTs have been investigated readily and management plans generated. Of all the patients with abnormal LFT results only a third have been referred to secondary care with two thirds being investigated or managed in primary care. iLFT has increased liver disease diagnosis, improved quality of care and reduced unnecessary secondary care referrals.